2011
DOI: 10.1177/1534735411425484
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin as Adjuvant Cancer Care With and Without Chemotherapy

Abstract: MLT may benefit cancer patients who are also receiving chemotherapy, radiotherapy, supportive therapy, or palliative therapy by improving survival and ameliorating the side effects of chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
59
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 139 publications
(64 citation statements)
references
References 33 publications
(52 reference statements)
1
59
0
4
Order By: Relevance
“…The majority of the results are positive, and melatonin has been described as an inhibitor of tumor growth under both in vitro and in vivo experimental conditions (64,81,97). The results arisen in the past few years also suggest that melatonin, either alone or along with chemotherapy in cancer patients diagnosed with advanced solid tumors, helps to improve the outcomes of cancer regression and life expectancy of the patients (122,128). Additionally, chemotherapies are typically better tolerated by patients who are simultaneously treated with melatonin (125).…”
Section: Melatonin and Cancer: What Next?mentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of the results are positive, and melatonin has been described as an inhibitor of tumor growth under both in vitro and in vivo experimental conditions (64,81,97). The results arisen in the past few years also suggest that melatonin, either alone or along with chemotherapy in cancer patients diagnosed with advanced solid tumors, helps to improve the outcomes of cancer regression and life expectancy of the patients (122,128). Additionally, chemotherapies are typically better tolerated by patients who are simultaneously treated with melatonin (125).…”
Section: Melatonin and Cancer: What Next?mentioning
confidence: 99%
“…A recent report concludes that melatonin combined with chemotherapy did not significantly improved survival or ameliorated various adverse side effects in patients with non-small cell lung advanced cancer, although certain improvement in the quality of life of these patients was observed (127). A systematic review comprising data from 21 clinical trials (all the patients enrolled in the studies were bearing solid tumors), in which the effect of melatonin concomitantly added in conjunction with chemotherapy or radiotherapy was evaluated, and supportive care, partial response, complete response, 1-year survival and chemotherapy-associated toxicities were assessed (128), concluded that melatonin may serve a beneficial role in cancer patients who are treated with chemotherapy. Patients who received melatonin experienced substantial improvements, particularly in terms of tumor remission and 1-year survival rates and melatonin also ameliorated the side effects of chemotherapy (127,128).…”
Section: Melatonin and Cancer: Clinical Trialsmentioning
confidence: 99%
See 3 more Smart Citations